2022
DOI: 10.1364/ol.443659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of roughness on surface plasmons propagation along deep and shallow metallic diffraction gratings

Abstract: The roughness of shallow or deep metallic diffraction gratings modifies the propagation of surface plasmon mode along the metallic-air interface. The scattering losses lead to a spectral or angular broadening of the surface plasmon resonance (SPR) and to a shift of the resonance wavelength and coupling angle. This mechanism is deeply analyzed both experimentally and theoretically to overcome these effects when such structures, in particular deep ones, are used as SPR-based sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…These reports have revealed that the light reflected at normal incidence from surface irregularities has much more precise optical information than that measured at oblique incidences. , We have used normal incident reflectance spectra for the Drude–Lorentz model to derive optical parameters of periodic nanostructures under the influence of surface irregularities (Supporting Information SI-3). Many authors ,,,, have previously used this technique to investigate the coupling mechanism of plasmons with photon- or exciton-induced diffractions that occurs either by wavenumber conservation (known as optical coupling) or by nonconservation of wavenumber (roughness coupling). As seen in the spectra of Figure (a), the variation of thickness and surface roughening has a consistent effect on the average reflectivity and its interference effects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These reports have revealed that the light reflected at normal incidence from surface irregularities has much more precise optical information than that measured at oblique incidences. , We have used normal incident reflectance spectra for the Drude–Lorentz model to derive optical parameters of periodic nanostructures under the influence of surface irregularities (Supporting Information SI-3). Many authors ,,,, have previously used this technique to investigate the coupling mechanism of plasmons with photon- or exciton-induced diffractions that occurs either by wavenumber conservation (known as optical coupling) or by nonconservation of wavenumber (roughness coupling). As seen in the spectra of Figure (a), the variation of thickness and surface roughening has a consistent effect on the average reflectivity and its interference effects.…”
Section: Resultsmentioning
confidence: 99%
“…The base sample E-0 consists of exclusive 2-D nanostructures that have streak spacing between layers and boundary edges, which maintained quasi-equilibrium in shear stress states to give lower values of surface roughness. 9,11 The progress of dual growth of corrugated particles along with vertical nanoflakes in E-50 leads to considerable change in surface texturing and film thickness to remarkably thrust the values of surface roughness toward a higher range. Similarly, the E-100 sample has the sole assembly of 3-D cubic nanostructures with a nonlinear spread of crack openings between edges, which further trivially raises the surface roughness.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction results in multiple reflections at the air/PEGT and PEGT/water interfaces, causing power loss. Additionally, roughness [ 32 ] and potential discrepancies between the permittivity of gold used in the software and that associated with the sample could partially explain the difference between theory and experiment.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The surface roughness of polished optical fibers still requires serious attention. According to several theoretical and experimental articles on prism-based configurations, the characteristic of the SPR curve is affected not only by the thickness [13] and homogeneity [14] of the metal layer but also by the roughness of the layer [15]. The methods and control parameters implemented during the deposition of the thin metal layer also play an important role [16].…”
Section: Introductionmentioning
confidence: 99%